Damage Identification on Impact and Lightning Damage of Flax Composite Laminates (Linum usitatissimum) Using Long-Pulse Thermography of a Low-Resolution Infrared Camera - Anwar, Murniwati; Mustapha, Faizal; Sultan, Mohamed Thariq H.; Halin, Izhal A.; Abdullah, Mohd N.; Hassim, Mohd I.; Mustapha, Mazli (Frontiers in Materials, 2021)
The demand for composite fiber material is significantly high due to its excellent mechanical properties and has been used in various industries. Recently, with the increasing awareness on the environmental issues, researchers are now focusing more on eco-friendly and green materials. Bio composite offers a good balance of strength and stiffness ratio, bending and membrane mechanical properties, balanced thermal distortion stability, reduced weight and cost, improved fatigue resistance, reduced notch sensitivity and comparatively having better performance compared to synthetic composite. Yet, due to their complex anisotropy of the composite material, the inspection and detection of inner defects become a challenge. Long pulse thermography is one of non-destructive evaluation to detect defect of composite materials However, very limited research into the usage of low-resolution infrared camera to perform defect damage inspection on Flax composite laminates. In this paper, an experimental set-up of Long Pulse thermography system using a low-resolution infrared camera of flax bio-composite on impact and lightning damage defects. The result highlight that with control parameters, a low-resolution infrared camera has the capability to capture lightning and impact defect of flax bio-composite defect using long pulse thermography system. An Image processing method is then applied to the defect to improve the quality of defect detection and reduce background noise.